Electrochemical performance of antimony/chlorine-incorporated nickel foam. Issue 48 (20th November 2019) - Tao, Keyu; Lv, Sen; Hai, Yang; Gong, Yun
Abstract : In this paper, an Sb/Cl-incorporated nickel foam (NF) electrode material was grown on acid-pretreated NF by one-step chemical vapor deposition using SbCl3 as the Sb source. Abstract : In this paper, an Sb/Cl-incorporated nickel foam (NF) electrode material was grown on acid-pretreated NF by one-step chemical vapor deposition using SbCl3 as the Sb source. The synthetic conditions can be optimized by adjusting the dosage of SbCl3 . The sample exhibits excellent electrochemical properties due to its unique morphology of porous nanosheet clusters, with a high specific capacity of 1248 C g −1 at 1 A g −1 and excellent rate performance (capacity retention of 70.5% at 10 A g −1 ). An asymmetric supercapacitor fabricated with Sb/Cl-incorporated NF and activated carbon exhibits a high energy density of 57.6 W h kg −1 at a power density of 1202 W kg −1 with good cycling stability. The capacity retention after 10 000 cycles is 83.3%. Given these characteristics, this work provides a simple and scalable strategy for designing an electrode and a device with superior electrochemical performance in next-generation energy storage applications.